Evaluation of a three-month trial of thyroxine replacement in symptomatic subclinical hypothyroidism: An impact on clinical presentation, quality of life and adoption of long-term therapy - Pandrc, Milena S.; Ristić, Andjelka; Kostovski, Vanja; Randjelović Krstić, Violeta; Milin Lazović, Jelena; Nedeljković Beleslin, Biljana; Ćirić, Jasmina (Vojnosanitetski pregled, 2021)
Background/Aim. Although subclinical hypothyroidism (SCH) is frequently a biochemical diagnosis, some symptoms and signs of overt disease may be present, influencing our decision to start the treatment with levothyroxine (LT4). The aim of this study was to examine the effect a 3-month LT4 treatment on clinical presentation and quality of life in symptomatic SCH with thyroid-stimulating hormone (TSH) < 10 mIU/L. We also considered whether treatment discontinuation additionally improves reliability of these findings. Methods. Clinical parameters (disease-specific score) and quality of life (Short Form-36 questionnaire) were measured in 35 patients with persistent symptomatic SCH (TSH 7.0 ± 2.1 mIU/L) before the intervention (LT4 substitution), 3 months after the euthyroid state had been achieved and 3 months after cessation of LT4 substitution. Results. The median of the Zulewski index significantly decreased after the treatment with LT4: 5.0 (4.0–7.0) vs. 3.0 (2.0–5.0) (p < 0.001) representing a reduction of symptoms. The most common ailments before the treatment were dry skin (71.4%), hoarseness (65.7%) and rough skin (54.3 %). After the treatment, there was a significant reduction in the frequency of constipation (p = 0.004), dry skin (p = 0.022), hoarseness (p = 0.002), decreased sweating (p = 0.006), and delayed Achilles reflex (p = 0.002). Quality of life was not changed significantly after LT4 treatment. In the group of 18 patients who discontinued the treatment, many symptoms and signs reappeared with the TSH increasing (6.8 ± 1.1 mIU/L): periorbital edema, constipation, weight gain, decreased sweating, slow motion and delayed Achilles reflex. The median of the Żulewski index after discontinuation of LT4 was 6.0 (4.0–9.0) (p = 0.010). Also, there was a statistically significant reduction in the general health score, and vitality, role emotional and mental health scores. Conclusion. Clinical score, based on symptoms and signs, is a sensitive and reproducible test for objective estimation of LT4 treatment effects in symptomatic SCH patients with TSH <10 mIU/L and supports individually adjusted treatment. Symptomatic SCH is not necessarily associated with a quality of life impairment that may be significantly improved by LT4 treatment. Changes in general health, vitality, mental health and emotional role after LT4 cessation suggest that some aspects of life quality can be affected by subtle variations in thyroxine availability.